Back to the workplace: How organisations can improve their support for management learning and development - Belling, Ruth; James, Kim; Ladkin, Donna (Emerald, 2004)
This paper explores how organisations can become more sophisticated at supporting transfer of learning, by identifying the perceived barriers and facilitators to transfer of learning, by examining a range of individual characteristics and workplace features associated with these barriers and facilitators and then relating these to the type of programme that managers undertake. The longitudinal survey methodology and programme typology used in the research are described. Findings highlight 26 perceived barriers and 17 facilitators to the transfer of learning, significant associations are shown with particular features such as mentoring and personal values. The paper goes on to identify the characteristics associated with a lack of transfer and suggests a tentative model of perceived influences on transfer of learning. Based on this research, it is concluded that it is important to take programme learning design into account when considering support for transfer of learning from management development programmes back to the workplace.